Standing up, falling down [videorecording (DVD)] - Crystal, Billy; Schwartz, Ben, 1981-; Mumford, Eloise (Shout! Factory, 2020)
A failing stand-up comedian and an alcoholic dermatologist give each other the confidence to face the failures in their lives.